Code-Mixing in Narrative Essay of Fifth Grade Students - Ginting, Carolin Eninta; Rahman, Rahman (Universitas Sebelas Maret, 2019)
This study aims to find out the code-mixing in narrative essays of grade 5th primary school and what factor is behind the use of code-mixing. This study is done in one of the school in Lembang sub-district which is most of the students are coming from provinces in Indonesia. Method of this study is descriptive analysis. The instrument of this study is a written test by giving an assignment to make a narrative essay. This study uses data analysis technique to analyze word by word, sentence, and phrase which contain code-mixing. This study states that some students’ narrative essays contain code-mixing. There are 8 narrative essays contain code-mixing. It is found that students mix Indonesian language and English, Indonesian language and local language such as Betawi and Sundanese, and formal and informal language. The factors of code-mixing in those narrative essays are the speaker and his personality, limitation of code, habituation, and more popular terms.